Operational Transconductance Amplifier Designed with SiGe-source Nanowire Tunnel-FET using Experimental Lookup Table Model - Nogueira, Alexandro De M.; Agopian, Paula G. D. [UNESP]; Simoen, Eddy; Rooyackers, Rita; Claeys, Cor; Collaert, Nadine; Martino, Joao A. (Institute of Electrical and Electronics Engineers (IEEE), 2020)
An Operational Transconductance Amplifier (OTA) circuit designed with SiGe-source nanowire Tunnel-FETs is presented for the first time. The results are compared with Si nanowire TFET and with Si nanowire MOSFET designs. The transistors were modeled using experimental data in order to obtain a lookup table and the Verilog-A language for the circuit simulation. It was observed that there is a trade-off between the open loop gain (AV0) and the gain-bandwidth product (GBW) of these circuits. The Si-nanowire MOSFET OTA presents the lowest AV0 but the best GBW, while the Si nanowire TFET OTA presents the highest gain but the lowest GBW. The SiGe-source nanowire TFET OTA studied in this paper achieves a better compromise, which is, a better open loop gain (88 dB) than the Si-nanowire MOSFET circuit and a better gain-bandwidth product (718 kHz) than the Si nanowire TFET OTA.
Keywords: analog circuits; lookup table; nanowire; OTA; SiGe; Tunnel-FET